Development of an experimental model bubbling fluidized bed combustor for combustion of biomass (2011)
Fuel flexibility and capacity to burn broad spectrum of fuels at high combustion efficiency with minimum emissions of greenhouse gases are few of several key advantages fluidized bed combustion technology has over other existing combustion technology. This report examines the design, development and testing of an experimental model Bubbling fluidized bed combustor (BFBC). The developed BFBC has unique inert bed's temperature regulating system which implies that the use of external source of cooling the inert bed such as embedded water cooled coil might be unnecessary. Fluidizing air pre-heater / Biomass feeding pipe's cooling attachment which attempt to prevent biomass from burning before entering the fluidized bed is another important feature of this BFBC. The Combustor body was fabricated from 150mm diameter, 2900mm tall type- 304 stainless steel pipes, divided into 5 modules. Coconut shell and Palm kernel shells were burnt successfully in the combustor. As a result of its numerous advantages over conventional combustion technology, Fluidized Bed Combustion (FBC) has been identified as a most viable means of generating renewable energy, therefore success with small BFBC like the one described here could be applied to building commercial size BFBC for power generation in Nigeria and Africa sub-region.